The Impact of Green Human Resource Management on Green Supply Chain Management: The Mediating Role of Green Life Style - Al Shaar, Eshaq (Jordan Journal of Business Administration, 2021)
This study aimed to identify the impact of green human resource management on green supply chain management in light of green life style. The population consisted of human resource management directors working in Jordanian industrial companies, located in the King Abdullah II Ibn Al-Hussein Industrial City in Jordan, while the study sample consisted of (215) directors. To achieve the study objectives, the analytical descriptive method was used. A questionnaire to collect data consisting of (30) items was developed. To test the study hypotheses, data was analyzed using Structural Equation Modeling (SEM). The results indicated that green human resource management (green development and training, green employee involvement and green performance management and appraisal) has a positive effect on green supply chain management. Moreover, the results of the study showed that green life style mediates the impact of green human resource management on green supply chain management. The study asserts on the importance of forming policies or strategies for green human resource management in Jordanian manufacturing companies that promote optimal use to reduce waste of resources. Furthermore, great attention has to be paid to green training and allocating a budget for preparing appropriate training programs to improve employees’ green knowledge to be applied on daily activities.